(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Wheat seeds (Triticum aestivum) are among the grains with a high lectin concentration. The sort with the highest lectin content had the lectin removed and purified. It was purified via fractionation with 60% NH3SO4 saturation then loadeded on DEAE-Cellulose column followed by Sepharose-6B size exclusion chromatography, and a yield of 61.5% with specific activity of 853.3 U/mg. Oral candidiasis led to the isolation of seven different Candida albicans isolates, all of which produced variable quantities of biofilm. With percentages of biofilm inhibition ranging from 23 to 44% with 50 µg/ml. The isolated lectin demonstrated antibiofilm efficacy against all Candida albicans isolates. The inhibition grew with increasing doses, reaching 65-88% at 200 µg/ml. such that lectin can be used to treat an oral cavity that is infected with Candida albicans.